The Development Process of Bipolar Bone Defects From Primary to Recurrent Instability in Shoulders With Traumatic Anterior Instability. Issue 3 (March 2019) - Nakagawa, Shigeto; Iuchi, Ryo; Hanai, Hiroto; Hirose, Takehito; Mae, Tatsuo
Background: Recurrence of glenohumeral joint instability after primary traumatic anterior instability is not rare, and bipolar bone loss is one of the most critical factors for recurrent instability, but the development process of bipolar bone defects is still unclear. Purpose: To investigate the development process of bipolar bone defects from primary to recurrent instability among shoulders with traumatic anterior instability evaluated at least twice by computed tomography (CT). Study Design: Case series; Level of evidence, 4. Methods: There were 44 patients (47 shoulders) with recurrence after primary instability in which bone morphology was evaluated by 3-dimensional reconstructed CT at primary instability (initial CT) and after recurrence. As CT was performed 3 times for 3 shoulders including primary injury and the second episode of instability (first recurrence), there were 50 CT evaluations. Morphological changes between the initial CT evaluation at primary instability and the second CT evaluation at first recurrence were investigated for 25 shoulders, with the mean interval since initial CT being 9.8 months (range, 2-23 months). Changes between initial CT evaluation and final CT evaluation after ≥2 recurrences were also investigated for 25 shoulders, while the mean number of instability episodes including primary instability was 8.0 (range, 3-40) and the mean interval since initial CT was 18.5 months (range, 5-56 months). Results: At primary instability, the prevalence of Hill-Sachs lesions (66.0%) was almost double that of glenoid defects (34.0%), but their prevalence was different between shoulders with primary subluxation (42.3% and 23.8%, respectively) and those with primary dislocation (84.7% and 42.3%, respectively). After recurrence, glenoid defects became significantly more frequent (at first recurrence, 72%; after ≥2 recurrences, 76%), while Hill-Sachs lesions showed a smaller increase (88% and 80%, respectively), so there was no difference between the prevalence of the 2 lesions. The sizes of glenoid defects and Hill-Sachs lesions also enlarged after recurrence, and large bone defects were frequently recognized after recurrence. While bipolar bone loss was not so frequent at primary instability (29.8%), bipolar bone loss increased significantly after recurrence (at first recurrence, 72%; after ≥2 recurrences, 72%). All Hill-Sachs lesions were on track at primary instability, but off-track lesions were recognized in 3 of 47 shoulders (6.4%) after recurrence. Conclusion: In most shoulders with recurrent instability, a Hill-Sachs lesion developed first, followed by a glenoid defect, leading to bipolar bone loss. Off-track Hill-Sachs lesions were detected only after recurrence.